ESG (Environmental, Social, Governance) performance and its impact : which role will financial institutions play in order to build a more sustainable access to financial loans and other forms of credit in the future? - Lambertz, Nick (2022)
In the context of a more responsible, sustainable economy, the concept of Sustainable Finance is gaining more and more of attention. Despite the increasing research, the concept lacks clarity regarding its implementation. The present research aims to analyse the implications of ESG metrics and its performance on the refinancing situation of companies additionally to questions on which role financial institutions will play hereby. Data has been collected through a comprehensive review of the literature, complemented by interviews with senior experts of more sustainable-driven financial institutions (Banks, the largest stock exchange, ESG data consultancy). The analysis reveals the necessity of clear, practical guidelines for a transformation of impact measurements into a combination of revenue, value, and impact metrics. Additionally, refinancing requires a long-term focus, customer centricity and a high degree of transparency.